(untitled) (Pedagogy of Higher and Secondary Education, 2004)
Play is conceded as one of the facilities an adaptation of the society personality of younger schoolboy on the strength of its age and psychological-physiological particularities. Described main function of play in the adaptation teaching to the social ambience.